A Qualitative Study into Teachers' Experiences with Emergency Distance Learning at The Start of The Covid-19 Pandemic - Hasna ELKHANNOUBI; Daniel TOMIUK; Mukesh SRIVASTAVA (Communications of International Proceedings, 2022)
With the COVID-19 pandemic, distance learning was quickly adopted by universities to continue providing students with courses during lockdowns. This emergency transition from traditional classroom to online teaching created unique and challenging experiences for teachers. We are conducting a qualitative study using focus groups to understand teachers' technology choices, difficulties, and strategies employed to effectively deliver courses online at the pandemic’s start. Our preliminary results corroborate the importance of universities providing instructors with technological solutions high in system quality that allow instructors to deliver high in content quality, all while providing technological help and support. These parallel the factors identified in the Delone & McLean (2003) model. However, our study also evidences the importance of collaboration and mutual aid among instructors which played an important role in the adoption of technologies and the success of moving to distance learning. Our findings suggest that special attention must be paid to this factor to ease the transition to online teaching by universities.
Keywords: Distance learning; e-learning; pandemic; teachers’ experiences